Influence of Foliar Applied Gaba on Growth And Yield Contributing Characters of White Gourd (Benincasa Hispida) - Ali, M. Musabber; Md Ashrafuzzaman,; Ismail, M. R.; Shahidullah, S. M.; Prodhan, A. K. M. A. (2010)
An experiment was conducted to investigate the effect of GABA on growth, yield and yield attributes of white gourd. The concentrations of GABA were 0.5 mg L-1, 1.0 mg L-1, 1.5 mg L-1 and 2.0 mg L-1 along with the control (no hormone). GABA was applied as foliar spray at 60 days after planting. Result showed that GABA had positive regulatory effect on growth, yield and yield contributing characters of white gourd. GABA @ 1.0 mg L-1 was the best for vine length, leaf length, leaf breadth, number of internodes, number of nodes at which first male and female flower appeared, number of male and female flowers per plant, number of seeds per fruit, weight of 100 seeds, seed length, number of fruits per plant, weight of fruits per plant and total yield of fruits. It was concluded that GABA @ 1.0 mg L-1 as foliar spray could be the suitable concentration for enhancing growth and yield of white gourd.